Utilization of Windu Shrimp Shell Waste from Malaka-NTT for Chitosan Synthesis: Characterization Study and Application Potential - Kedang, Yohana Ivana; Oktavianawati, Ika; Tea, Marselina Theresia Djue (BERKALA SAINSTEK, 2024)
Chitosan is a non-toxic and biodegradable polymer compound. Chitosan is widely applied in various industrial fields. This research uses shrimp shell waste from the Malaka-NTT as a chitin and chitosan production source. Chitosan synthesis consists of three steps, namely deproteination, demineralization and deacetylation. Chitosan characterization includes determining the degree of deacetylation (DD), determining functional groups using Fourier Transform Infra-Red (FTIR), and measuring crystallinity using X-ray diffraction (XRD). The DD results obtained were 83.7%. The FTIR spectra results of the chitosan samples in this study showed a typical peak at absorption of 1648 cm-1 indicating the vibration of the C=O group in NHCOCH3 (amide) I and absorption of 1589 cm-1 indicating the vibration of the N-H bending group (amide II). The results of the XRD diffractograms on the chitosan sample show an orthorhombic crystal structure with two typical peaks, namely at angles 2Î¸ = 10.12Â° and 2Î¸ = 19.87Â°. The DD results obtained in this study indicate that the chitosan produced has a fairly high amine group content, so chitosan as a biomaterial has the potential to be applied in various pharmaceutical and biomedical fields because it has environmentally friendly, biocompatible, and biodegradable properties. Therefore, based on the results of the DD calculation and the characterization of the FTIR and XRD instruments in this study, it shows that the synthesis of chitosan from the utilization of tiger shrimp shell waste from Malaka Regency-NTT has been successfully carried out.